How much heat does non-photochemical quenching produce? - Murakami, Aoi; Kim, Eunchul; Minagawa, Jun; Takizawa, Kenji (Frontiers in Plant Science, 2024)
Non-photochemical quenching (NPQ) is a protective mechanism used by plants to safely dissipate excess absorbed light energy as heat, minimizing photo-oxidative damage. Although the importance of NPQ as a safety valve for photosynthesis is well-known, the physiological and environmental effects of the heat produced remain unclear because the amount of heat produced by NPQ is considered negligible, and its physiological effects have not been directly observed. Here, we calculated the heat produced by NPQ and evaluated its impact on the leaf and global warming based on simplified models. Our evaluation showed that the heat produced by NPQ in a given leaf area is 63.9 W m -2 under direct sunlight. Under the standard condition, NPQ warms up the leaf at less than 0.1°C, but it could be 1°C under particular conditions with low thermal conductance. We also estimated the thermal radiation of vegetation's NPQ to be 2.2 W m -2 par global averaged surface are. It is only 0.55% of the thermal radiation by the Earth's surface, but still significant in the current climate change response. We further discuss the possible function of NPQ to plant physiology besides the safety valve and provide strategies with artificial modification of the NPQ mechanism to increase food production and mitigate global warming.